Influence End Stamp to Efficiency Turbine Wind Savonius Four Spoons - Japheth Bontong (Inspire Global Insight Journal, 2026)
The pattern of energy consumption which is constantly increasing over time causes scarcity energy so that almost all Country race for awaken energy from source - source energy new and renewable. Wrong One The chosen energy is wind energy. This study aims to examine the characteristics of the vertical Savonius type wind turbine by finding Torque, Power windmill, performance windmill use end stamp and without end stamp. From results study obtained data at speed wind 1.2 m/s without end stamp produce Power maximum as big as 0.0385 watt and torque maximum 0.00245 Nm and maximum efficiency of %. while at wind speed of 1.2 m/s using the end cap maximum power of 0.07701 watts and maximum torque of 0.00491 Nm and maximum efficiency of %. From these results it can be concluded that turbine wind Savonius four blade use end stamp more Good compared without end stamp.